Review on Consistency as a Service: Auditing Cloud Consistency (CAAS Model) - Shyam P Dubey, Nilesh Chaubey, Rupesh C Bichwe, (International Journal of Scientific Research and Management (IJSRM), 2015)
In day to day life cloud is most essential part. Now cloud storage are use for business purpose the cloud is popular due to their huge amount of advantages the cloud is portable we can able to access the cloud anywhere globally. A cloud service provider maintains much duplication and each piece of data are globally distributed on servers. The main problem of cloud is to handle duplication of data which is too costly to achieve powerful consistency on world wide .In this paper we present a novel consistency service model which contain a large amount of data cloud and multiple audit clouds In The Consistency Service model. A data cloud is maintain by Cloud service Provider (CSP) and the number of user constitute group and that group of user can constitute an audit cloud Which can check whether the data cloud provides the valid level of consistency or not we suggest the two level auditing architecture, two level auditing architecture requires a loosely synchronize clock in the audit cloud. Then, design algorithms to quantify the commonality of violations metrics, and the staleness of the value of a read metrics. Finally, we devise a heuristic auditing strategy (HAS) to reveal as many violations as possible. Extensive experiments were performed using a combination of simulations and real cloud deployments to validate heuristic Auditing Strategy.